Evaluation of the GHRH–arginine retest for young adolescents with childhood-onset GH deficiency. (April 2016) - Dreismann, Laura; Schweizer, Roland; Blumenstock, Gunnar; Weber, Karin; Binder, Gerhard
Abstract: Objective: Retesting of adolescents with childhood-onset GH deficiency (GHD) is recommended, but age-related reference data are scarce. We aimed to establish a cut-off value for the GHRH–arginine test (GHRH + ARG) at the typical age of retesting at near-adult height. Designs: We retrospectively studied 149 patients (108 males) with childhood-onset GHD aged 16.8 ± 1.7 years (mean ± SD) with a BMI of 20.9 ± 3.5 kg/m 2 who had received GHRH + ARG in one single center during 8 consecutive years. Based on the IGF-I serum concentration falling below − 2 SDS when off GH, 22 patients suffered from severe GHD of adulthood while 122 were GH sufficient. Five patients could not be determined definitively. GH and IGF-I were measured by in-house RIAs. IGF-I values were transformed into age-related SDS values. ROC-analysis was used to determine the cut-off value. Results: For GHRH + ARG, a cut-off limit of 15.9 ng/ml had the highest pair of sensitivity (91%) and specificity (88%). GH peaks of the patients with a normal BMI between − 1 and 0 SDS were higher than those with a high BMI > 1 SDS ( p < 0.01). Conclusions: When retesting adolescents at near-adult height for severe GHD of adulthood, a GH value of < 15.9 ng/ml in GHRH + ARG is discriminatory with good accuracy. Conversion factors for other GH assays in use are provided. A rational decision for or against the continuation of GH therapy into adulthood can be made based on the clinical history of the patient and the combination of the GHRH + ARG retest result and the IGF-I serum concentrations when off GH. Highlights: The study proposes the first GH cut-off for the GHRH + ARG re-test for the group of young adolescents at near-adult height. The adaptation of the GH cut-off value to widely used GH assays is described. The GHRH + ARG re-test maxima were negatively correlated to BMI.